Features of uranium distribution in sediments of Pur-Tazovsky oil-and-gas area (northeast of Western Siberia) - Elena Isaeva; Nellie Feodorovna Stolbova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the discussed issue is caused by the necessity to solve the problems associated with the heterogeneity of the reservoir, with the impermanence of filtration-capacitive parameters, with the absence of a relationship between permeability and open porosity, to identify effectively oil and gas deposits. The main aim of the work is to allocate the features of uranium distribution in oil-and-gas deposits in northeast of Western Siberia. The material and methods used in the study. To understand the pressing issues on the study of hydrocarbons accumulation it is necessary to clarify and supplement the information content of geophysical methods with geochemical (nuclear physics), mineralogicalpetrographic and other methods of research. The authors use the laboratory data permeability and open porosity, in conjunction with geochemical indicators of the uranium distribution to identify dependencies between them. The object of the research is a Jurassic-Cretaceous sediments (2330 samples), opened by seven deep wells drilled in the North-East of the West Siberian plate, on-site Purtazowskoy oil-and gas-bearing area. The results. It is revealed that the change of porosity and permeability of hydrocarbon deposits are affected most of all by dislocation and metasomatic processes, which result in formation of heterogeneous zones of dissolution and cementation. The prediction of prospective collector areas is actually associated with the prediction of zones of intensive development of these processes. It is possible to identify such intervals with the help of uranium distribution regularities. The prospective deposits are characterized, as a rule, by extremely low U contents (less than 1,5 g/t), the presence of epibitumens, signs of dissolution and corrosion of rubble and cement. The authors attempted to identify the areas of prospective reservoirs in the well Vankor-11 based on uranium geochemical behavior.